(3EOGQI GdeYQaI h fXe GdeYdheGJ (B/s - (3GdNWjH, GMeOs; (3RjZGf, NGdOs ((3YeGf(B: s (3YGde GdcJH GdMOjK(B, s, 2009)
(3EOGQI GdeYQaI h fXGe gPg GdEOGQI , EOGQI fXe GdeYdheGJ (B: (3OQGSI aj GdbWGY GdJQHhj , fXGe GdeYdheGJ GdGOGQjI h fXe GdeYdheGJ GdJQHhjI , GdJLGQH GdeMdjI aj GdCQOf , GdYdGbI eG Hjf fXe EOGQI GdeYdheGJ h JMOjO GdSjGSGJ GdJQHhjI (B.s
(3eQGLY U(B.225 (3; edGMb U(B.195s
Keywords: (3GdeYQaIs; (3fXe GdeYdheGJ GdEOGQjIs; (3fXe GdeYdheGJ(B- (3GdeDSSI GdeeJOI s